Workplace energy conservation at Michigan State University. Issue 1 (2nd January 2018) - Allen, Summer; Marquart-Pyatt, Sandra T.
Abstract : Purpose: This research contributes to the literature on workplace energy conservation by examining the predictors of individual employee behaviors and policy support in a university. The purpose of this research is to better understand what factors influence energy conservation behaviors in this setting to inform programs and interventions. Design/methodology/approach: This project gathered survey data from employee-occupants of three campus buildings. Ordinary least squares regression analyses were used to investigate the theory of planned behavior (TPB) and attitudes-behavior-constraints (ABC) models examining what drives energy behaviors. Findings: This study finds a large proportion of respondents would support energy use reduction policies, more technology-based interventions and increased use of renewable sources. Respondents report positive attitudes toward individual energy conservation behavior but mild agreement with the influence of social norms. Self-efficacy reports also are positive. Although the TPB model is not fully supported in this group, the ABC model appears to perform well. Originality/value: In addition to adding to the relatively limited data on employee energy-saving behaviors in the university workplace, this study provides initial evidence that the ABC model is pertinent to this behavioral context. It also provides specific, usable data about policies and actions that campus community members might deem feasible and acceptable to relevant university offices.